Diseño de un sistema de gestión de la calidad para el mejoramiento de los procesos productivos de la empresa Touch Of Flowers EC. en la parroquia de Joseguango Bajo - Iza Niza, Ronny Orlando (2022)
The purpose of this research work is the design of a quality management system in the company TOUCH OF FLOWERS EC, to improve production processes through partial compliance with the requirements of ISO 9001: 2015. A visit was made to the company to identify the activities that comply in the processes and through the diagnosis of evaluation of the standard the current situation was identified, the study was carried out through the type of bibliographical and field research, applying the analytical method - synthetic since it allowed the fulfillment of the activities, using the techniques of, interview, check list and observation, for a correct collection of information, and through the results obtained it was possible to develop the process diagrams. The assessment obtained after completing the diagnostic evaluation of the ISO 9001: 2015 standard, showed the shortage of documentation for compliance with the requirements and the design of the quality management system is proposed through the creation of new documents needed based on the requirements established in the standard. The research allowed the implementation of new tasks within the design, which are found written in the manual so that the company can improve and offer quality processes, it is concluded that workers have optimal information of the activities they perform in each of the processes and through the percentage obtained of 16% in the evaluation diagnosis indicates that the respective design of the quality manual should be carried out.